The Contributions of Protein Kinase A and Smoothened Phosphorylation to Hedgehog Signal Transduction in Drosophila melanogaster - Zhou, Qianhe (Copyright © 2006 by the Genetics Society of America, 2006)
Protein kinase A (PKA) silences the Hedgehog (Hh) pathway in Drosophila in the absence of ligand by phosphorylating the pathway's transcriptional effector, Cubitus interruptus (Ci). Smoothened (Smo) is essential for Hh signal transduction but loses activity if three specific PKA sites or adjacent PKA-primed casein kinase 1 (CK1) sites are replaced by alanine residues. Conversely, Smo becomes constitutively active if acidic residues replace those phosphorylation sites. These observations suggest an essential positive role for PKA in responding to Hh. However, direct manipulation of PKA activity has not provided strong evidence for positive effects of PKA, with the notable exception of a robust induction of Hh target genes by PKA hyperactivity in embryos. Here we show that the latter response is mediated principally by regulatory elements other than Ci binding sites and not by altered Smo phosphorylation. Also, the failure of PKA hyperactivity to induce Hh target genes strongly through Smo phosphorylation cannot be attributed to the coincident phosphorylation of PKA sites on Ci. Finally, we show that Smo containing acidic residues at PKA and CK1 sites can be stimulated further by Hh and acts through Hh pathways that both stabilize Ci-155 and use Fused kinase activity to increase the specific activity of Ci-155.